Polo-like kinase acts as a molecular timer that safeguards the asymmetric fate of spindle microtubule-organizing centers - Matellán, Laura; Manzano-López, Javier; Monje-Casas, Fernando (eLife, 2020)
The microtubules that form the mitotic spindle originate from microtubule-organizing centers (MTOCs) located at either pole. After duplication, spindle MTOCs can be differentially inherited during asymmetric cell division in organisms ranging from yeast to humans. Problems with establishing predetermined spindle MTOC inheritance patterns during stem cell division have been associated with accelerated cellular aging and the development of both cancer and neurodegenerative disorders. Here, we expand the repertoire of functions Polo-like kinase family members fulfill in regulating pivotal cell cycle processes. We demonstrate that the Plk1 homolog Cdc5 acts as a molecular timer that facilitates the timely and sequential recruitment of two key determinants of spindle MTOCs distribution, that is the γ-tubulin complex receptor Spc72 and the protein Kar9, and establishes the fate of these structures, safeguarding their asymmetric inheritance during Saccharomyces cerevisiae mitosis.